RESISTIRE D4.3 Summary report on qualitative indicators - cycle 3 - Sandström, Lina; Callerstig, Anne-Charlott; Strid, Sofia; Lionello, Lorenzo; Rossetti, Federica (Zenodo, 2023)
The aim of RESISTIRÉ is to understand the unequal impacts of the COVID-19 outbreak and its policy and societal responses on behavioural, social and economic inequalities and to work towards individual and societal resilience. RESISTIRÉ does so by collecting and analysing policy data, quantitative data and qualitative data in the EU27 (except Malta), Iceland, Serbia, Turkey and the UK, and translating these into insights to be used for designing, devising and piloting solutions for improved policies and social innovations, which in turn can be deployed by policymakers, stakeholders and actors in the field across different policy domains. The project relies on an eleven-partner multidisciplinary and multisectoral European consortium and a well-established network of researchers in 30 countries. Throughout the course of RESISTIRÉ, research conducted consistently show how already vulnerable and marginalised groups have become even more vulnerable and marginalised; existing inequalities have increased, and new ones have emerged (Axelsson et al. 2021; Cibin et al. 2021, 2022; 2023; Harroche et al. 2023; Sandström et al. 2022; Stovell et al. 2021, 2022). Significantly less overall attention has been paid to practices that may transform inequalities and very little attention has been given to individual agency. The third and final research cycle in RESISTIRÉ therefore looked to the future and shifted focus to individual ‘better stories’ (Georgis 2013; Altınay 2019) and strategic forms of agency (Lister 2004, 2021) of marginalised groups during the pandemic. With an analytical focus on gender+ inequalities, this report addresses the following overall research question: What kind of agency is practiced, or available to practice, by individuals and street-level bureaucrats, with an emphasis on what enables and what hinders strategic agency? The report is based on two methods of qualitative data collection: narrative interviews with individuals strategically recruited based on their marginalised or vulnerable profile and ...